The COVID-19 pandemic and regional economic resilience in northern Finland, Norway, and Sweden – bouncing back or not? - Simonen, Jaakko; Moilanen, Mikko; Kotila, Jemina; Lohtander, Joona; Westin, Lars; Hersinger, Anders; Østbye, Stein; Riepponen, Tapio; Svento, Rauli (Luleå tekniska universitet, Industriell ekonomi, 2023)
The COVID-19 pandemic has been first and foremost a health crisis, but it has also had severe negative impacts on the global economy. It has shaken regional economies, especially labour markets, over the last two years. Arctic regions are no exception. The aim of this article is to analyse the regional economic impacts, as well as the recovery processes, of the COVID- 19 pandemic in Arctic 5 cities in Northern Finland, Sweden, and Norway (Oulu and Rovaniemi in Finland, Luleå and Umeå in Sweden and Tromsø in Norway). In many countries, including Finland, Sweden and Norway, governments decreed various types of lockdown policies to prevent the spread of the COVID-19 pandemic. Due to such policies, the pandemic has had an asymmetrical impact not only on individuals but also on communities and regions. This has given new urgency to a place-based approach to regional development, mitigating territorial inequalities. Our goal is to study how hard the Arctic 5 cities have been hit by the COVID-19 shock and how well they have been able to absorb, adapt to and recover from the crisis. The research question thus focuses on the resilience of the regions. In this study, we focus on the analysis of public statistics concerning the development of labour markets. We also analyse changes in human behaviour during the pandemic using the information provided by Google Mobility data. These mobility data and labour market indicators are used to measure regional economic and social resilience. Our research shows that, for example, regional socioeconomic structures have played an important role in how well the regions have been able to withstand the pandemic and recover from it. Differences in national containment regulations have also affected this development. These cross-border comparisons provide information on how well different measures in different regions across national borders have functioned and what impacts they have had on regional economies, especially on labour markets and people’s mobility. Validerad;2023;Nivå ...